Pengembangan Kapasitas Kelembagaan Pemerintah Daerah dalam Meningkatkan Kualitas Pelayanan Perizinan Terpadu (Studi pada Kantor Pelayanan dan Perizinan Terpadu Kabupaten Kediri) - Novita Sari (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2014)
Abstract: Institutional Capacity Building of Local Government in Improving Quality Integrated Licensing Service (Study at the Office of Services and Integrated Licensing Kediri Regency). In encouraging the growth of the area, each area must maintain and improve the investment climate. Kediri has a substantial investment, the number of entrepreneurs and investors who are interested in making the necessary existence of licensing services. Quality of service is the service good effect on clearance in Kediri. Thus the necessary institutional capacity building, in the Office of Integrated Services and Licensing Kediri for services that have not been a problem but the door to licensing issues fairly good views of Community Satisfaction Index for the year 2013. The institutional capacity should be improved from the increase in human resources and inadequate infrastructure, regulation is not in accordance with the current licensing conditions of service. Besides institutional capacity building program has been running well, among others, an increase in disciplinary apparatus, human resources quality improvement activities to improve service quality investments, improving the investment climate and realization. Keywords: Capacity Building, Institutional, Public Service. Abstrak: Pengembangan Kapasitas Kelembagaan Pemerintah Daerah dalam Meningkatkan Kualitas Pelayanan Perizinan Terpadu (Studi pada Kantor Pelayanan dan Perizinan Terpadu Kabupaten Kediri). Dalam mendorong pertumbuhan daerah, setiap daerah harus menjaga dan memperbaiki iklim investasi. Kabupaten Kediri memiliki investasi cukup besar, banyaknya pengusaha dan investor yang berminat sehingga diperlukan adanya pelayanan perizinan. Kualitas pelayanan yang berpengaruh terhadap baiknya layanan izin di Kabupaten Kediri. Demikian diperlukan pengembangan kapasitas kelembagaan, Di Kantor Pelayanan dan Perizinan Terpadu Kabupaten Kediri untuk masalah pelayanan yang belum satu pintu tetapi masalah perizinan cukup baik dilihat dari Indek Kepuasan Masyarakat selama tahun 2013. Masalah kapasitas kelembagaan harus diperbaiki dari peningkatan SDM dan sarana prasarana yang kurang memadai, peraturan belum sesuai dengan kondisi pelayanan perizinan saat ini. Selain itu program pengembangan kapasitas kelembagaan sudah berjalan baik antara lain peningkatan disiplin aparatur, kegiatan peningkatan kualitas SDM guna meningkatkan kualitas pelayanan investasi, peningkatan iklim investasi dan realisasi. Kata Kunci: Pengembangan Kapasitas, Kelembagaan, Pelayanan Publik.